THE CONCEPT OF “ORDER” IN SPAIN (1770-1870) - Chacón Delgado, Pedro José (Revista de Historia Social y de las Mentalidades, 2011)
The concept of ‘order’ permits an investigation into not only the disposition of the components of a political space such as Spain during the period under question (1770-1870), but also how political actors perceived the space in which they moved. Within this period there was a substantial change in what had previously been regarded as the natural order as established by God, as a result of the events which led to the approval of the 1812 Constitution. From this point onwards the political scene underwent a profound transformation, with the appearance of the intellectual elites, in opposition to the defenders of the Old Regime, as well as the first inklings of social revolution, within a context of continual changes of constitution and government, virtually until the Restoration of 1875. The concept of order also clashes with the concept of liberty, as the juxtaposition of both definitions was the real key of political debate throughout 19th-century Spain.